Aberrant mechanical loading induces annulus fibrosus cells apoptosis in intervertebral disc degeneration via mechanosensitive ion channel Piezo1 - Chenhao Liu; Xiaoxin Gao; Jinhui Lou; Haiyin Li; Yuxuan Chen; Molong Chen; Yuyao Zhang; Zhilei Hu; Xian Chang; Menglin Luo; Yu Zhai; Changqing Li (Arthritis Research & Therapy, 2023)
Abstract Background Intervertebral disc degeneration (IVDD) is closely associated with the structural damage in the annulus fibrosus (AF). Aberrant mechanical loading is an important inducement of annulus fibrosus cells (AFCs) apoptosis, which contributes to the AF structural damage and aggravates IVDD, but the underlying mechanism is still unclear. This study aims to investigate the mechanism of a mechanosensitive ion channel protein Piezo1 in aberrant mechanical loading-induced AFCs apoptosis and IVDD. Methods Rats were subjected to lumbar instability surgery to induce the unbalanced dynamic and static forces to establish the lumbar instability model. MRI and histological staining were used to evaluate the IVDD degree. A cyclic mechanical stretch (CMS)-stimulated AFCs apoptosis model was established by a Flexcell system in vitro. Tunel staining, mitochondrial membrane potential (MMP) detection, and flow cytometry were used to evaluate the apoptosis level. The activation of Piezo1 was detected using western blot and calcium fluorescent probes. Chemical activator Yoda1, chemical inhibitor GSMTx4, and a lentiviral shRNA-Piezo1 system (Lv-Piezo1) were utilized to regulate the function of Piezo1. High-throughput RNA sequencing (RNA-seq) was used to explore the mechanism of Piezo1-induced AFCs apoptosis. The Calpain activity and the activation of Calpain2/Bax/Caspase3 axis were evaluated by the Calpain activity kit and western blot with the siRNA-mediated Calapin1 or Calpain2 knockdown. Intradiscal administration of Lv-Piezo1 was utilized to evaluate the therapeutic effect of Piezo1 silencing in IVDD rats. Results Lumbar instability surgery promoted the expression of Piezo1 in AFCs and stimulated IVDD in rats 4 weeks after surgery. CMS elicited distinct apoptosis of AFCs, with enhanced Piezo1 activation. Yoda1 further promoted CMS-induced apoptosis of AFCs, while GSMTx4 and Lv-Piezo1 exhibited opposite effects. RNA-seq showed that knocking down Piezo1 inhibited the calcium signaling pathway. CMS enhanced Calpain activity and elevated the expression of BAX and cleaved-Caspase3. Calpain2, but not Calpain1 knockdown, inhibited the expression of BAX and cleaved-Caspase3 and alleviated AFCs apoptosis. Lv-Piezo1 significantly alleviated the progress of IVDD in rats after lumbar instability surgery. Conclusions Aberrant mechanical loading induces AFCs apoptosis to promote IVDD by activating Piezo1 and downstream Calpain2/BAX/Caspase3 pathway. Piezo1 is expected to be a potential therapeutic target in treating IVDD.